KUALITAS PELAYANAN MUSEUM GEOLOGI BANDUNG: SUATU STUDI MENGENAI PERSEPSI WISATAWAN DOMESTIK - Noor, Any; Karwina, Wiwin (Universitas Pendidikan Indonesia, 2011)
Geological Museum, Bandung is an educational and historical tourist attraction that mostly visited by student. As tourist attraction, Geological Museum should deliver good services in order to satisfy tourists. In order to understand the tourist perception about service quality in Geological Museum, this study aim to explore the tourist perception about service quality delivered at Geological Museum. Five dimensions of service quality which are reliability, responsiveness, empathy, assurance and tangible were asked to 127 respondents through questionnaire at Geological Museum, Bandung. Findings indicate that responsiveness dimension is the lowest point of service quality and tangible is at the highest point, although result of both dimensions is at medium level. In overall, tourist perception about Geological Museum service quality is at medium level and has the potential to be good in services.